Spatial-temporal distribution of the black rhino population in the Ngorongoro Crater, Tanzania - Gadiye, Donatus; W. Eshiamwatta, George; O. Odadi, Wilfred (International Journal of Biological Research, 2016)
Ngorongoro Conservation Area (NCA) is vital especially for black rhino conservation because it is one of the only two ecosystems in Tanzania that host native black rhino populations. However, the spatial-temporal distribution of rhinos in this ecosystem have not been assessed. The purpose of this study was to assess the temporal and spatial distribution of rhinos and factors responsible for the uneven seasonal distribution. The study was conducted in Ngorongoro Conservation Area (NCA) which is located at 3°12′S, 35°27′E during the wet (May-June 2015) and dry (August-September 2015) sampling periods. Road drives were conducted daily for a period of one month during each season to map the spatial distribution of the black rhino, and assess the relative abundance of its forage resources and diet selection. During each drive, the roadsides were inspected for the presence of rhinos, with stops being made each time an individual or group of rhinos is located. Results shows that the distribution patterns of the black rhino differed markedly between wet and dry sampling periods. During the dry period, rhinos were mainly concentrated in the crater slopes dominated by shrubby vegetation, swamps and along riverine areas of the crater. During wet season in there were more herbage material mostly preferred by black rhino in crater floor as most rhinos were sighted in these sampling areas. Human activities such as tourism infrastructure (lodges, campsites and roads) should be kept minimal to minimize disruption to rhino movement and habitat selection patterns and buffer zones be established within crater-community interfaces where human activities such as livestock grazing are strictly prohibited to ensure natural distribution ranges are maintained.